Three new crab spiders from Xishuangbanna Rainforest, southwestern China (Araneae: Thomisidae) - Tang, Guo; Li, Shuqiang (Zootaxa, 2009)
This study deals with three new crab spiders, Alcimochthes meridionalis sp. nov., Lycopus primus sp. nov. and Oxytate capitulata sp. nov., all from Xishuangbanna Rainforest, Yunnan, China. The genus Lycopus Thorell, 1895, formerly described from females only, is reported from China for the first time in both sexes.